Epitranscriptomic Regulations in the Heart - Benak, D; Kolar, F; Hlavackova, M (Physiological research, 2024)
RNA modifications affect key stages of the RNA life cycle, including splicing, export, decay, and translation. Epitranscriptomic regulations therefore significantly influence cellular physiology and pathophysiology. Here, we selected some of the most abundant modifications and reviewed their roles in the heart and in cardiovascular diseases: N6-methyladenosine (m6A), N6,2'-O-dimethyladenosine (m6Am), N1-methyladenosine (m1A), pseudouridine (?), 5 methylcytidine (m5C), and inosine (I). Dysregulation of epitranscriptomic machinery affecting these modifications vastly changes the cardiac phenotype and is linked with many cardiovascular diseases such as myocardial infarction, cardiomyopathies, or heart failure. Thus, a deeper understanding of these epitranscriptomic changes and their regulatory mechanisms can enhance our knowledge of the molecular underpinnings of prevalent cardiac diseases, potentially paving the way for novel therapeutic strategies. Keywords: Epitranscriptomics, RNA modifications, Epigenetics, m6A, RNA, Heart.
Keywords: Transcriptome; epigeneze genetická; myokard; Adenosine; Animals; Humans; Epigenesis, Genetic; Myocardium; lidé; posttranskripční úpravy RNA; zvířata; RNA Processing, Post-Transcriptional; adenosin; transkriptom